Tricks and tacks in the management of the forgotten double J stent - Agarwal, Shikhar; Sarpal, Rajeev; Pathak, Priyank; Biswas, Manoj; Mittal, Ankur; Rathore, Karamveer; Pal, Ravinder (International Surgery Journal, 2018)
Background: Double J ureteral stent has become the part and parcel of the routine procedure for the prevention or relief of upper urinary tract obstruction. Forgotten DJ stent can lead to encrustation, infection, migration, hydronephrosis and fragmentation. Methods: Total 16 patients with forgotten double J stent at urology department of the tertiary teaching hospital from January 2014 to December 2016 were included in this retrospective study. The details reviewed included the indwelling time, presenting complaints, radiological and laboratory investigations, their management techniques and complications of the interventions. Results: Twelve were male while 4 were female with mean patient age was 41.3±10 years. Most common presenting complaints were lower urinary tract symptoms. Five had broken stent, two encrusted calcified stents while two were migrated to upper ureter. One patient was diagnosed as pyonephrosis while 6 patients were uncomplicated cases. Conclusions: Stents, which are forgotten, can lead to morbidity in stented patients. Stent register should be made, and a computer-based tracking system has also been described to ensure the safety.